Right Ventricular Remodeling and Dysfunction in Obstructive Sleep Apnea: A Systematic Review of the Literature and Meta-Analysis - Abdirashit Maripov; Argen Mamazhakypov; Meerim Sartmyrzaeva; Almaz Akunov; Kubatbek Muratali uulu; Melis Duishobaev; Meerim Cholponbaeva; Akylbek Sydykov; Akpay Sarybaev (Canadian Respiratory Journal)
Background. Recent studies have reported that obstructive sleep apnea (OSA) patients present alterations in right ventricular (RV) structure and function. However, large randomized controlled trials evaluating the impact of OSA on the right ventricle are lacking. Methods. A comprehensive electronic database (PubMed, Web of Science, and Google Scholar) and reference search up to October 30, 2016, was performed. A systematic review and meta-analysis were performed to assess RV structure and function in OSA patients based on conventional echocardiography and tissue Doppler imaging. Results. Twenty-five studies with 1,503 OSA patients and 796 controls were included in this study. OSA patients exhibited an increase in RV internal diameter (weighted mean difference (WMD) (95% confidence intervals (CIs)) 2.49 (1.62 to 3.37); p=0.000) and RV wall thickness (WMD (95% CIs) 0.82 (0.51 to 1.13); p=0.000). Furthermore, OSA patients had a significantly elevated RV myocardial performance index (WMD (95% CI) 0.08 (0.06 to 0.10); p=0.000), decreased RV S’ (WMD (95% CI) −0.95 (−1.59 to −0.32); p=0.003), tricuspid annular plane systolic excursion (WMD (95% CI) −1.76 (−2.73 to −0.78); p=0.000), and RV fractional area change (WMD (95% CI) −3.16 (−5.60 to −0.73); p=0.011). Conclusion. OSA patients display RV dilatation, increased wall thickening, and altered RV function.